Methodological Role of Philosophy - Meškauskas, Eugenijus (Problemos, 1990)
In the paper the role of methodological ideas in the development of philosophy is analysed. Based upon the analysis done an inference is drawn, that the actual value of philosophical theories consists not in the particular explanations of the reality but rather in the productivity of the methodological ideas, opening the ways for the further research. The inference substantiates the Marxist calling for the inclusion of the development of dialectical methodology into the object of the contemporary philosophy.